Retrospective evaluation of percutaneous tracheostomy cases performed by griggs method in intensive care unit (Annals of Medical Research, 2021)
Aim: Tracheostomy is frequently performed after prolonged endotracheal intubation in intensive care units (ICU). Percutaneous tracheostomy (PT) is often preferred because it is a less invasive bedside aplicable procedure and the complication rate is lower. The aim of this study is to present our experience of PT interventions in ICU.Material and Methods: Between January 2016 and March 2019, patients who underwent PT by Griggs method were evaluated retrospectively. Age, gender, length of ICU stay, hospitalization diagnoses, timing for tracheostomy, complications related to the procedure and discharge / death status of the patients were recorded.Results: Eighty-nine patients were examined. The mean age of the patients was 59.4 ± 19.5 years, and the mean length of ICU stay was 80.3 ± 10.2 days. Tracheostomy was most commonly performed for neurological disorders. Duration of intubation was 20.3 ± 4.5 days. Complications developed in 8 patients (8.9%). The most common complication was minor bleeding (3.3%). Mortality developed in 59 patients (66.2%); 9 patients (10.1%) were discharged to the palliative service and 8 patients (8.9%) were discharged home. The mean length of ICU stay was 80.3 ± 10.2 days in tracheostomized patients, 56.4 ± 8.9 days in discharged patients and 92.5 ± 12.5 days in patients who died.Conclusion: In our study, performing day of tracheostomy was found to be higher. This may be due to patient relatives' ignorance of tracheostomy. By giving trainings to patients’ relatives, tracheostomy may be performed earlier and complications due to late performed tracheostomy can be prevented.